Misinformation or education? A comparative analysis of Instagram posts related to full mouth rehabilitation - Alfaraj, Amal; Alshahrani, Faris A.; Albalawi, Meshal; AlQahtani, Naif; Alhajji, Mohammed; Alharbi, Ali Sulaiman; Ainoosah, Sultan; Al-Khalifa, Khalifa S. (Frontiers in Dental Medicine, 2025)
IntroductionSocial media platforms have become pivotal in health communication, with Instagram serving as a key channel for sharing medical and dental information. Full Mouth Rehabilitation (FMR), a complex treatment aimed at restoring oral function and aesthetics, remains underrecognized by the general public. This study investigates the nature and accuracy of Instagram content related to FMR.MethodsA cross-sectional content analysis was conducted on 144 Instagram posts using FMR-related hashtags. Posts were classified based on content type, poster role (e.g., dental professional, clinic, influencer), engagement metrics (likes, comments), and accuracy of information. Statistical tests were applied to assess variations across content categories.ResultsMarketing-oriented content constituted the majority of posts (75.7%), while educational content accounted for only 9%. Most posts (86.8%) contained non-factual or misleading information. In contrast, all educational posts were factually accurate. Engagement levels did not significantly differ between factual and non-factual posts. Dental professionals were responsible for only 5.6% of the total content, reflecting a notable lack of expert presence.DiscussionInstagram holds significant potential for disseminating accurate dental health information. However, the dominance of promotional content and the low involvement of dental professionals contribute to a high prevalence of misinformation. To enhance the platform's reliability as a health communication tool, increased participation by dental experts and improved content oversight are essential. Future research should evaluate strategies for promoting evidence-based information on social media, particularly for advanced procedures like FMR.